The Aged Woman as Specter in Two Filmic Adaptations of "Snow White". - Whitehurst, Katherine (Marvels & Tales, 2018)
This article examines the filmic fairy-tale adaptations Mirror Mirror (2012) and Snow White and the Huntsman (2012) by unpacking the films' depictions of female ageing. The article demonstrates how the films frame the aged woman as a spectral, atemporal figure who resides within the logic of the disappearing older woman in postfeminist popular culture. It demonstrates how the films expand the central conflict beyond Snow White and the queen to multiple generations of women, illustrating how these adaptations feed into generational frictions and perpetuate the erasure of the older woman on screen through the intersection of form and content.